Association of abdominal obesity to hypertension history in Panamanian college students - Rangel Caballero, Luis Gabriel; Irribaren Llorente, Lourdes Luz; Vásquez Mendoza, Natalie Patricia; Ardines Bailey, Isabel Anayansi; Murillo López, Alba Liliana (Archivos Latinoamericanos de Nutrición (ALAN), 2024)
Introduction: Abdominal obesity is the excess of deposits of fat in the abdominal region and it is an independent risk factor for cardiovascular disease. Hypertension is a metabolic risk factor for non-communicable diseases, and it is the leading cause of premature death in the world. Objective: to determine the association between abdominal obesity and hypertension, hyperglycemia, and hyperlipidemia history in Panamanian college students. Materials and methods: Analytical cross- sectional study carried out in 434 college students from four different cities of a private university in Panamá. Every participant in the study signed written consent. Abdominal obesity was established as a waist circumference of ≥80 cm in women and ≥90 cm in men. Hypertension, hyperglycemia, and hyperlipidemia history were established with the basic questionnaire in the STEPS World Health Organization Instrument. Descriptive, as well as bivariate and multivariate analysis, were realized using logistic regression models. Results: 36.41% of participants had abdominal obesity (no statistically significant difference was found by sex). 14.29%, 9.22%, and 13.82% of the students surveyed reported a history of hypertension, hyperglycemia, and hyperlipidemia respectively (no statistically significant difference was found by sex). After adjusting by sex, age, and socioeconomic level, abdominal obesity was associated with hypertension antecedent (OR=2.06, CI 95%: 1.183-3.597, p=0.011). Conclusions: Students who evidenced abdominal obesity were more likely to have a hypertension history. The study recommends implementing strategies that promote healthy living habits to reduce future cardiovascular risk in the Panamanian university population. Introducción: La obesidad abdominal es el exceso de grasa en la región abdominal y un factor de riesgo de enfermedad cardiovascular. La hipertensión es un factor de riesgo metabólico asociado a enfermedades no transmisibles, y es la causa principal de muerte prematura en el mundo. Objetivo: Determinar la asociación entre la obesidad abdominal y los antecedentes de hipertensión, hiperglucemia e hiperlipidemia en universitarios panameños. Materiales y métodos: Estudio transversal analítico realizado en 434 universitarios de cuatro ciudades de una universidad privada de Panamá. Cada participante firmó el consentimiento informado. La obesidad abdominal fue establecida con una circunferencia de la cintura ≥80 cm en mujeres and ≥90 cm en hombres. Los antecedentes de hipertensión, hiperglucemia e hiperlipidemia fueron establecidos mediante el Cuestionario Básico del Instrumento STEPS de la OMS. Análisis descriptivos, bivariados y multivariados fueron realizados utilizando modelos de regresión logística. Resultados: El 36,41 % de los participantes registró obesidad abdominal (no hubo diferencia estadísticamente significativa según sexo): El 14,29 %, 9,22 % y el 13,82 % de los participantes reportaron antecedente de hipertensión, hiperglucemia e hiperlipidemia respectivamente (no hubo diferencia estadísticamente significativa según sexo). Después de ajustar por sexo, edad, y nivel socioeconómico, la obesidad abdominal se asoció con el antecedente de hipertensión (OR=2,06, IC 95 %: 1,183-3,597, p=0,011). Conclusiones: Los estudiantes que evidenciaron obesidad abdominal tuvieron una mayor probabilidad de antecedente de hipertensión. Se recomienda la implementación de estrategias para promover hábitos saludables y reducir el riesgo cardiovascular en la población universitaria panameña.